Analysis and comparison of some aquatic motor behaviors in young children - Michielon, G.; Scurati, R.; Roione, G. C.; Invernizzi, P. L. (Biomechanics and Medicine in Swimming X, 2006)
Several studies considered aquatic motor sequences in young children and their relations with some aspects of aquatic psychomotor development. The aim of this study was to understand if spontaneous swim movements of the child can evolve into an effective action, after a "keep doing" and a "free exploration" based methodological approach. Three groups of ten children, different in age (4-12 months, 12-24 months, 24-36 months), were studied. The presence of some motor skills pre and post a period of 10 events of free experience in a swimming pool were detected. No differences were found in the prepost comparison within each group. Differences resulted in the comparison of the children aged 4-12 versus 24-36 months and in the children aged 12-24 versus 24-36 months.